Temperature testing climate action: what are the impacts of social and economic factors on local climate action in the UK? - M. Spiers; S.A. Price; J. Powell-Turner (Sustainable Communities)
Introduction Social and economic factors influence human behaviour at the individual and community levels. This study examines how variables such as sense of community, well-being, income, and deprivation impact climate-action behaviours. It provides an initial investigation into behaviours as “actions” taken by people, individually and with their communities, under different social and economic conditions. Answering the primary research question, “Do social cohesion and socio-economic indicators impact climate action at the individual and community levels?”Materials and methods A convenience sample of 105 participants from the UK was obtained for this study, comprising 84 online responses and 21 in-person responses. Independent variables representing social cohesion included well-being (WHO-5) at the individual level and sense of community (Brief Sense of Community Scale) at the community level. Socioeconomic position was assessed using income (bands) and deprivation (Indices of Multiple Deprivation). Each of these were grouped in accordance with the scale, and a MANOVA was conducted to analyse the effects of these groups against the dependent variables of individual and community climate actions.Results Multivariate analysis revealed that the sense of community groups and income groups significantly impacted climate action. Univariate tests of between-subjects effects indicated that the effect of sense of community was only significant on community climate action and post-hoc fishers LSD revealed the high sense of community group was varying from Low and Moderate sense of community. Income was found in post hoc analysis to have no significant differences between income groups. Wellbeing and Deprivation groups did not have an impact on climate action.Conclusion The findings highlight the importance of fostering a high sense of community through needs fulfilment, belonging, influence, and connection, to promote sustainable climate action behaviours and move towards a Net Zero Society. Sense of community as a social cohesion indicator, emerged as a key driver and the piece recommends collaborating with communities to track real-time behavioural and social change. Limitations of the research are the sample size and localised geography, yet it is argued that a place-based approach is needed in future social cohesion and climate action research.